2018
DOI: 10.14778/3229863.3236232
|View full text |Cite
|
Sign up to set email alerts
|

The return of jedAI

Abstract: JedAI is an Entity Resolution toolkit that can be used in three ways: (i) as an open-source library that combines state-of-the-art methods into a plethora of end-to-end workflows, (ii) as a user-friendly desktop application with a wizardlike interface that provides complex, out-of-the-box solutions even to lay users, and (iii) as a workbench for comparing the performance of numerous workflows over both structured and semi-structured data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…For instance, Dong and her collaborative researchers proposed a probabilistic schema integration approach in [32], as well as data fusion approaches that consider data sources correlation in sort of data duplication [23][24][25]37]. Moreover, research efforts related to probabilistic entity linkage and resolution can be found at [9,10,[38][39][40][41][42][43][44][45][46].…”
Section: Data Integrationmentioning
confidence: 99%
“…For instance, Dong and her collaborative researchers proposed a probabilistic schema integration approach in [32], as well as data fusion approaches that consider data sources correlation in sort of data duplication [23][24][25]37]. Moreover, research efforts related to probabilistic entity linkage and resolution can be found at [9,10,[38][39][40][41][42][43][44][45][46].…”
Section: Data Integrationmentioning
confidence: 99%
“…Without a doubt, the last two decades have been characterized by massive production of data with regards to the fields of Computer Science (CS) and Artificial Intelligence (AI). Several real-life applications contribute to this phenomenon, operating as rich sources of data over all possible kinds: structured, semi-structured or unstructured [1,2]. We distinguish the next fields: social media platforms, economic transactions, medical recordings and Internet of Things (IoT) where Industry 4.0, constitutes a highly affected application coming from the latter field [3][4][5].…”
Section: Introductionmentioning
confidence: 99%